2017
DOI: 10.1093/cid/ciw763
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality of Patients With Tuberculous Meningitis in New York City: A Cohort Study

Abstract: Among patients with culture-confirmed TBM, we observed rapid early mortality in patients with rifampin-resistant isolates, and an independent association between isoniazid-resistant isolates and death after 60 days of therapy. These findings support the continued evaluation of rapid diagnostic techniques and the empiric addition of second-line drugs for patients with clinically suspected drug-resistant TBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…8,9 INH is a cornerstone medication in the therapy of TBM, and patients with INH resistance have significantly worse outcomes. [10][11][12][13] The patient's initial TBM treatment did not include an adequate course of INH, and there was concern for recurrence. TB affects the spine predominantly in the form of extramedullary disease.…”
Section: Infectiousmentioning
confidence: 99%
“…8,9 INH is a cornerstone medication in the therapy of TBM, and patients with INH resistance have significantly worse outcomes. [10][11][12][13] The patient's initial TBM treatment did not include an adequate course of INH, and there was concern for recurrence. TB affects the spine predominantly in the form of extramedullary disease.…”
Section: Infectiousmentioning
confidence: 99%
“…Among HIV-infected patients, the rate of mortality from TBM may reach more than 60.0% (6). TBM caused by drug-resistant strains of Mycobacterium tuberculosis has a mortality rate approaching 100% (7). The presenting clinical features of TBM are similar to those of other forms of subacute meningoencephalitides, making clinical diagnosis difficult and contributing to TBM's high mortality risk due to a delay in starting treatment (8,9).…”
mentioning
confidence: 99%
“…The magnitude of the association between initial isoniazid resistance and death was similar among 186 HIV-infected tuberculous meningitis patients in Vietnam, with the additional finding that excess mortality due to isoniazid resistance did not emerge until after the first 60 days of treatment [112]. Interestingly, this time-dependent relationship between isoniazid resistance and death was also observed among tuberculous meningitis patients in New York City, USA [113•] (Fig. 3).…”
Section: Drug-resistant Tuberculous Meningitismentioning
confidence: 74%
“…Among participants in the clinical trial of dexamethasone in Vietnam, 14% demonstrated severe disability at 5 years of follow-up, with no difference between the dexamethasone and placebo arms [71]. Among HIV-uninfected tuberculous meningitis patients in New York City who successfully completed treatment, there was no additional mortality burden when compared to population age- and sex-matched controls over a 10-year follow-up period, although differences in neurologic morbidities that did not impact survival were not measured [113•]. A multistate cohort study of 806 US tuberculous meningitis patients, conducted using administrative claims data, identified rates of neurologic complications at 1 year following diagnosis for stroke (15%), seizures (12%), and visual impairment (19%) [121].…”
Section: Long-term Neurologic Outcomes Among Survivorsmentioning
confidence: 99%